PENGARUH PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL PRODUKSI JAGUNG MANIS (Zea mays saccharata Sturt.) DI LAMPUNG UTARA - Nyang Vania Ayuningtyas Harini; Yeyen Ilmiasari; Refky Sanjaya; Eko Abadi Novrimansyah; Septa Febrianti (AGRORADIX : Jurnal Ilmu Pertanian, 2023)
Sweet corn (Zea mays saccsharata Sturt.) is one of the plants that is widely produced and a source of food staples in Indonesia, such as processed food, drinks, and so on. The low productivity of sweet corn in North Lampung is caused by the use of excessive doses and the wrong fertilization method. This problem can be overcome by implementing a good cultivation system, including applying fertilization with the right dosage so that plants can produce according to their potential results.The purpose of this study was to determine the effect of NPK fertilizer treatment on the growth and yield of sweet corn at the best dose of NPK fertilizer on the growth and yield of sweet corn. This research was conducted experimentally using RAL (Completely Randomized Design). It consists of one factor with 3 levels, namely K0: Control, K1: Giving NPK 150 kg/ha (1.8 kg/plant plot) K2: Giving NPK 300 kg/ha (3.6 kg/plant plot).The results showed that the NPK treatment had a significant effect on plant height at 30 HST. The stem diameter showed a significant effect when the sweet corn was 30 and 45 HST. The number of leaves shows that NPK fertilizer has no real effect. The length of the cobs with husks, the length of the cobs without husks, the weight of the husked cobs, the weight of the cobs without husks and the weight of the stover showed real results.